The Effects of the Grafting Time and Types on the Success of the Grafted Grapevine Production by Grafting Under Nursery Condition; Fidanlik Şartlarinda Aşilama Yoluyla Aşili Asma Fidani Üretiminde Başan Üzerine Aşi Tipi Ve Aşilama Zamanlarinin Etkileri - Çelik, Hüseyin; Odabaş, F. (TÜBİTAK, 1998)
This study has been carried out to determine the effects of grafting time and types on success of grafted grapevine production by grafting under nursery condition during 1992-1994. After planting the cuttings taken from the Kober 5BB and SO4 (Vitis berlandieri x Vitis riparia) American hybrid rootstocks into the nursery plots like establishing the vineyard during spring time, they were grafted by omega and chip-budding grafting type using the buds and a single node cuttings taken from the summer shoots of Alphonse Lavallée, Cardinal, Çavuş and Hafizali at the August. 15: September, 15; October, 15 and November, 15. The highest rate of take was 86.3% (Çavuş-SO4-Chip-budding-August, 15) and 100.0% (Alphonse Lavallée-SO4-Chip-budding-September 15), respectively to the years. The rate of sprouting was also the highest at the same cultivars and combination. 80.0% and 90.0% respectively to the years. The rate of rooted and grafted grapevine plantings and first grade grafted grapevine plantings were the highest on the grafts made at September, 15 on SO4 rootstock by chip-budding. The success of omega machine grafting was also as high as 76.7% (Alphonse Lavallée-Kober 5BB-Omega-September, 15).
Fidanlık Şartlarında Aşılama Yoluyla Aşılı Asma Fidanı Üretiminde Başarı Üzerine Aşi Tipi ve Aşılama Zamanlarının Etkileri